2016
DOI: 10.1371/journal.pone.0153972
|View full text |Cite
|
Sign up to set email alerts
|

Response of Plant Height, Species Richness and Aboveground Biomass to Flooding Gradient along Vegetation Zones in Floodplain Wetlands, Northeast China

Abstract: Flooding regime changes resulting from natural and human activity have been projected to affect wetland plant community structures and functions. It is therefore important to conduct investigations across a range of flooding gradients to assess the impact of flooding depth on wetland vegetation. We conducted this study to identify the pattern of plant height, species richness and aboveground biomass variation along the flooding gradient in floodplain wetlands located in Northeast China. We found that the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 51 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…The results suggest that not only wetland area but also wetland volume may be important for N removal. However, a higher plant production in shallow wetlands [17,[38][39][40] may promote N removal [36,37], which could not be tested in this short-term study. The results suggest that a low availability of P may, in some situations, limit N removal in wetlands receiving drainage water from agricultural fields.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The results suggest that not only wetland area but also wetland volume may be important for N removal. However, a higher plant production in shallow wetlands [17,[38][39][40] may promote N removal [36,37], which could not be tested in this short-term study. The results suggest that a low availability of P may, in some situations, limit N removal in wetlands receiving drainage water from agricultural fields.…”
Section: Discussionmentioning
confidence: 96%
“…We suggest that longer residence times in the deep wetlands in this short-term study promoted N removal. However, it is likely that shallow wetlands will successively develop more vegetation than deeper wetlands [39,40], and therefore, that positive effects on the N removal of vegetation in shallow wetlands will become more important in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Tilly et al (2015) showed that plant height had a very strong relation to biomass production of rice (R 2 : 0.72 to 0.91) and recommended the variable as a non-destructive estimator for biomass of paddy rice. In particular, the plant height influenced the aboveground biomass significantly as reported by Lou et al (2016), while this biomass could be responsible for evapotranspiration, therefore the plant height presented in Table 2 might explain the variations in soil water loss between two study soils.…”
Section: Resultsmentioning
confidence: 65%
“…About two-thirds of the land area suffers different degrees of flooding [14]. The waterlogging stress is a kind of water stress, and the water stress includes drought stress (moisture loss) and waterlogging stress (flood).…”
Section: Introductionmentioning
confidence: 99%